Topographic Guidance in Melt-Electrowritten Tubular Scaffolds Enhances Engineered Kidney Tubule Performance - van Genderen, Anne Metje; Jansen, Katja; Kristen, Marleen; van Duijn, Joost; Li, Yang; Schuurmans, Carl C. L.; Malda, Jos; Vermonden, Tina; Jansen, Jitske; Masereeuw, Rosalinde; Castilho, Miguel (Frontiers in Bioengineering and Biotechnology, 2021)
Introduction: To date, tubular tissue engineering relies on large, non-porous tubular scaffolds (Ø > 2 mm) for mechanical self-support, or smaller (Ø 150-500 m) tubes within bulk hydrogels for studying renal transport phenomena. To advance the engineering of kidney tubules for future implantation, constructs should be both self-supportive and yet small-sized and highly porous. Here, we hypothesize that the fabrication of small-sized porous tubular scaffolds with a highly organized fibrous microstructure by means of melt-electrowriting (MEW) allows the development of self-supported kidney proximal tubules with enhanced properties. Materials and Methods: A custom-built melt-electrowriting (MEW) device was used to fabricate tubular fibrous scaffolds with small diameter sizes (Ø = 0.5, 1, 3 mm) and well-defined, porous microarchitectures (rhombus, square, and random). Human umbilical vein endothelial cells (HUVEC) and human conditionally immortalized proximal tubular epithelial cells (ciPTEC) were seeded into the tubular scaffolds and tested for monolayer formation, integrity, and organization, as well as for extracellular matrix (ECM) production and renal transport functionality. Results: Tubular fibrous scaffolds were successfully manufactured by fine control of MEW instrument parameters. A minimum inner diameter of 1 mm and pore sizes of 0.2 mm were achieved and used for subsequent cell experiments. While HUVEC were unable to bridge the pores, ciPTEC formed tight monolayers in all scaffold microarchitectures tested. Well-defined rhombus-shaped pores outperformed and facilitated unidirectional cell orientation, increased collagen type IV deposition, and expression of the renal transporters and differentiation markers organic cation transporter 2 (OCT2) and P-glycoprotein (P-gp). Discussion and conclusion: Here, we present smaller diameter engineered kidney tubules with microgeometry-directed cell functionality. Due to the well-organized tubular fiber scaffold microstructure, the tubes are mechanically self-supported, and the self-produced ECM constitutes the only barrier between the inner and outer compartment, facilitating rapid and active solute transport.